TINJAUAN ANTROPOLOGI HUKUM DAN MAQASHID AL-SYARIAH TENTANG PERKAWINAN USIA DINI - Abdurrahman Hakim (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
This research aims to analyze the existence of the asynchronous between the reality of the law in society and the existing law in the legislation concerning early marriage. For this reason, this research will be examined using the anthropological of law as an approach to find out three important aspects as objects of study of legal anthropology, namely knowledge of the community about law, the culture of community law, and the behavior of community law. After that, the case of early marriage will be analyzed using the theory of Maqhasid al-sharia. There are two reasons why this research needs to be studied using the theory of maqasid shariah. First, Law No. 1 of 1974 concerning Marriage is a manifestation of Islamic Law. Second, the community considers that early marriage is part of the teachings of Islam because it was once practiced by the Prophet and Aisha. The research method used is descriptive qualitative with the type of library research. The data used are legislation, books, newspapers, journals, and online media.